Signal perception by the secretion stress-responsive CssRS two-component system in Bacillus subtilis. - DEVINE, KEVIN; BOTELLA, ERIC (My University, 2012)
The CssRS two-component system responds to heat and secretion stresses in Bacillus subtilis by controlling expression of HtrA and HtrB chaperone-type proteases and positively autoregulating its own expression. Here we report on the features of the CssS extracellular loop domain that are involved in signal perception and on CssS subcellular localization. Individual regions of the CssS extracellular loop domain contribute differently to signal perception and activation. The conserved hydrophilic 26-amino-acid segment juxtaposed to transmembrane helix 1 is involved in the switch between the deactivated and activated states, while the conserved 19-amino-acid hydrophobic segment juxtaposed to transmembrane 2 is required for signal perception and/or transduction. Perturbing the size of the extracellular loop domain increases CssS kinase activity and makes it unresponsive to secretion stress. CssS is localized primarily at the septum but is also found in a punctate pattern with lower intensity throughout the cell cylinder. Moreover, the CssRS-controlled HtrA and HtrB proteases are randomly distributed in foci throughout the cell surface, with more HtrB than HtrA foci in unstressed cells.
PUBLISHED
Keywords: Bacillus subtilis.